2014
DOI: 10.1007/s12032-014-0918-3
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenicity of the transcription factor SOX8 in hepatocellular carcinoma

Abstract: SOX genes play an important role in a number of developmental processes. SOXs have been demonstrated to have potential roles as either tumor suppressors or promoters in various neoplastic tissues depending on the tumor status and type. The aim of this study was to investigate the functional role of SOXs in human cancers. Gene expression changes of SOXs in human hepatocellular carcinoma (HCC) tissues were detected using real-time quantitative reverse transcriptase-polymerase chain reaction (qRT-PCR) analysis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 25 publications
1
24
0
Order By: Relevance
“…SOX8 is a regulator of the Wnt/β‐catenin signaling pathway, and consistent with this information, we observed reduced β‐catenin staining in both CAL27‐res and SCC9‐res shSOX8 cells compared to their corresponding parental cells. A decrease of C‐myc levels and an increase of Dkk1 levels were observed in chemoresistant cells infected shSOX8 compared to uninfected cells (Supporting Information Figs.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…SOX8 is a regulator of the Wnt/β‐catenin signaling pathway, and consistent with this information, we observed reduced β‐catenin staining in both CAL27‐res and SCC9‐res shSOX8 cells compared to their corresponding parental cells. A decrease of C‐myc levels and an increase of Dkk1 levels were observed in chemoresistant cells infected shSOX8 compared to uninfected cells (Supporting Information Figs.…”
Section: Resultssupporting
confidence: 90%
“…29,30 Previous studies in hepatocellular carcinoma and gliomas have demonstrated that SOX8 promotes cell growth through the activation of Wnt/b-catenin signaling. 21,31 Xie et al also reported that SOX8, as a target of miR-124b, is overexpressed in lung cancer and closely associated with a poor prognosis. 32 In addition, we found that SOX8 expression correlated with lymph node metastasis rate and poor survival time in 103 TSCC patients and was higher especially in chemoresistant TSCC patients than in chemosensitive patients, indicating its potential value in chemoresistance.…”
Section: Disscussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Towards this goal, putative target genes of miR-139 were screened using bioinformatics methods. Among those genes, Sox8, belonging to group E of SOX family proteins, is reported to promote cell proliferation of diverse cancer cells [31, 32]. Several researchers have reported that Sox8 is expressed in the developing heart [33, 34].…”
Section: Discussionmentioning
confidence: 99%
“…There are few reports on soX8 in cancer. Zhang et al reported that soX8 promoted cancer cell proliferation in vitro and that its expression correlated with elevated β-catenin levels in hepatocellular carcinoma 90 .…”
Section: Mirnas Involved In Lymph Node Metastasismentioning
confidence: 99%